The Influence of using articulate storyline media on learning interest and results - Megawati Idris; Suwito Eko Pramono; Arief Yulianto (Inovasi Kurikulum, 2025)
Based on observations at SDN Palebon 03, Semarang City revealed problems in social studies learning. The problem is that the learning does not attract students' interest. Teachers still use lecture techniques, causing students to lose focus and only understand a small amount of the material. This research aims to determine whether Articulate Storyline media influences students' interest and learning outcomes in social studies subjects. This type of research is quantitative. The sample used was 30 class IV students. The data collection techniques used were questionnaires and tests. The data analysis used is descriptive analysis techniques and inferential analysis techniques. The results of descriptive statistical analysis show that the average initial score of students has increased after being given treatment. The results of the inferential statistical analysis of Articulate Storyline media on interest through testing show significant values. Meanwhile, the significant value of the Articulate Storyline media on learning outcomes also shows significance. It can be concluded that the Articulate Storyline media significantly influences the interest and learning outcomes in regional cultural wealth material for class IV students at SDN Palebon 03. Articulate Storyline can be utilized in classroom learning and further explored in learning and teaching activities.   Abstrak Berdasarkan Observasi yang dilakukan di SDN Palebon 03 Kota Semarang mengungkapkan permasalahan dalam pembelajaran IPS. Permasalahan tersebut yakni pembelajaran yang dilakukan kurang menarik minat siswa. Guru masih mengajar menggunakan teknik ceramah, menyebabkan siswa kehilangan fokus, dan hanya memahami sedikit materi. Penelitian ini bertujuan untuk mengetahui ada tidaknya pengaruh penggunaan media Articulate Storyline terhadap minat dan hasil belajar mata pelajaran IPS siswa. Jenis penelitian ini adalah kuantitatif. Sampel yang digunakan sebanyak 30 siswa kelas IV. Teknik pengumpulan data yang digunakan adalah angket dan tes. Analisis data yang digunakan adalah teknik analisis deskriptif dan teknik analisis inferensial. Hasil analisis statistik deskriptif menunjukkan bahwa rata-rata nilai awal siswa mengalami peningkatan setelah diberikan perlakuan. Hasil analisis statistic inferensial media Articulate Storyline terhadap minat melalui pengujian menunjukkan nilai yang signifikansi. Sedangkan nilai signifikansi media Articulate Storyline terhadap hasil belajar juga menunjukkan signifikansi. Dapat disimpulkan bahwa media Articulate Storyline memiliki pengaruh yang signifikan terhadap minat dan hasil belajar pada materi kekayaan budaya daerah siswa kelas IV SDN Palebon 03. Articulate Storyline dapat dimanfaatkan tidak hanya dalam pembelajaran kelas saja, articulate storyline dapat dieksplorasi lebih jauh penggunaanya dalam kegiatan belajar dan mengajar Kata Kunci: hasil belajar; mengartikulasikan alur cerita; minat belajar